Regional Social Infrastructure Management as the Instrument for Improving the Quality of Life in the Ural Federal District - Antonyuk, Valentina Sergeyevna; Danilova, Irina Valentinovna; Mitelman, Semen Arkadyevich; Bulikeyeva, Anara Zholaushobayevna (Economy of Regions, 2015)
The article analyzes the processes of the social sphere and the effective operation of social infrastructure in order to improve the quality of life of the population in the Russian regions. Particular attention is paid to the role of the organizational and managerial component affecting usage performance of infrastructure objects and including regulation of the institutions of social infrastructure, planning and software. The purpose of the study is to evaluate the effectiveness of management of social infrastructure through the conjugation of immediate results (the dynamics of indicators of social services) and outcomes (parameters of the quality of life of the population). The hypothesis of the study was the violation of the principle of infra-systematicity in the infrastructural support of the improvement of the quality of life in the Russian regions, due to the lack of effectiveness of public administration. In the study, the following methodological approaches are used: structural, factoral, systematic and evolutionary approaches to justify the conception, develop methodology and determine the impact of changes in the parameters of social infrastructure availability for the provided services, shifts in indexes of quality of life. The paper proposes the quantitative evaluation of the effectiveness of organizational management based on the diagnosis of the adequacy of the implementation of the principle of infra-systematicity in the functioning of social infrastructure on the basis of the elasticity coefficient. The proposed approach and the received analytical data on health, education, commerce, housing, culture and sport fields have allowed to range the regions of the Ural Federal District and highlight the areas of insufficient effectiveness of the organizational and management tool for improvement of life quality. The findings of the research may serve as a core for practical recommendations for executive bodies of administrative units of the Russian Federation and adjustment of socio-economic policy.